2006
DOI: 10.1101/gr.4999906
|View full text |Cite
|
Sign up to set email alerts
|

RNA expression profiling at the single molecule level

Abstract: We developed a microarray platform for PCR amplification-independent expression profiling of minute samples. A novel scanning system combined with specialized biochips enables detection down to individual fluorescent oligonucleotide molecules specifically hybridized to their complementary sequence over the entire biochip surface of cm2 size. A detection limit of 1.3 fM target oligonucleotide concentration—corresponding to only 39,000 molecules in the sample solution—and a dynamic range of 4.7 orders of magnitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
77
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(81 citation statements)
references
References 18 publications
3
77
0
1
Order By: Relevance
“…This is impressive, as different microarray platforms often do not show high concordance. Hesse et al (2006) also demonstrate that the dynamic range of single molecule detection is superior to conventional methods. The range of mRNA abundance levels in biological systems can approach 6 orders of magnitude, which clearly cannot be addressed by the ∼10 3 dynamic range of current microarray experiments.…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…This is impressive, as different microarray platforms often do not show high concordance. Hesse et al (2006) also demonstrate that the dynamic range of single molecule detection is superior to conventional methods. The range of mRNA abundance levels in biological systems can approach 6 orders of magnitude, which clearly cannot be addressed by the ∼10 3 dynamic range of current microarray experiments.…”
mentioning
confidence: 82%
“…A recent study (Hesse et al 2006) has shown the application of a fast CCD scanning method to a conventional long oligomer microarray spotted on a nonconventional slide, at a resolution that enables individual molecules to be resolved. Although individual Cy3 and Cy5 dye molecules-which are the labels most commonly used in microarray experiments-emit enough photons to be detected by a typical microarray scanner, scanners are not set up to resolve molecules individually.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, a single-molecule approach to DNA microarrays has been developed [40], as have high-throughput [41] and single-molecule [42][43][44] DNA sequencing methods. These examples are only a few of the many ways in which TIRF has been applied, and new uses for this simple yet versatile technique continue to emerge.…”
Section: Applicationsmentioning
confidence: 99%
“…The determination of protein density on the SU-8 surface was carried out in a custom built single molecule scanner based on a conventional inverted epi-fluorescence microscope (Axiovert 200 M, Zeiss, Germany) (Hesch et al 2009;Hesse et al 2006;Hesse et al 2004). The DyLight650…”
Section: Characterization Of Su-8 Surfacesmentioning
confidence: 99%